Criticism of the LMKN–LMK Dualism in Music Royalties Management in Indonesia - Mays Amelia (Jurnal Mengkaji Indonesia, 2025)
Abstract: The management of music royalties in Indonesia through the mechanisms of the National Collective Management Institution (LMKN) and the Collective Management Institution (LMK) shows serious problems in the context of copyright protection. Normatively, Article 9 paragraph (1) of Law No. 28 of 2014 grants creators exclusive rights to enjoy the economic benefits of their creations. However, the bureaucratic practices of LMKN-LMK actually reduce the meaning of these exclusive rights and shift the orientation of protection from creators to the managing institutions. This condition creates injustice because the legal system prioritizes institutional legitimacy over fulfilling the economic rights of creators. Purpose: The purpose of this study is to reconstruct the legal model for managing music royalties so that it returns to the core of copyright, namely justice for creators. Design/Methodology/Approach: This study is a normative legal study using a legislative approach, a conceptual approach, and a comparative approach. Findings: The results of the study indicate that the management model in Indonesia needs to be reformed through a revision of Law No. 28 of 2014 by eliminating the dualism of LMKN-LMK, strengthening an independent institution that is strictly supervised, and implementing technology-based digital transparency such as blockchain. Originality/value: The main finding is that the current legal system renders royalties an administrative-repressive instrument, rather than an instrument of distributive justice. Therefore, a legal reconstruction is needed that prioritizes transparency, accountability, and strengthens the position of creators as the primary subjects of copyright protection. This way, royalty distribution can function fairly, proportionally, and align with the principles of distributive justice.